Análisis de estrategias didácticas utilizadas para la integración curricular de físico-química en el séptimo semestre de la carrera de Biología, Química y Laboratorio en el periodo marzo-julio 2015 - Orozco Lluilema, Doralisa Alexandra (2016)
The investigation relates to the analysis of “Teaching strategies used for curricular integration of Physics-Chemistry in the seventh semester of the School of Biology, Chemistry and Laboratory during the period of March-July 2015”. The problem inquires ¿Are there any limitations in the use of teaching strategies for curriculum integration? This is because the education system has shortcomings in the application of educational processes by not focusing on new methods and teaching strategies, which is why an investigation on what type of teaching strategies should de used for curriculum integration. Research, ICT, Laboratory and the student portfolio are of upmost necessity, forcing teachers to respond to new educational challenges, and allowing students to develop in a better way their knowledge, skills and abilities. This work was base don a quasi –experimental research since there is a before and an after. The investigation is based on field research and documentary which included diagnostic and exploratory research. This study was conducted on a population of thirteen students an research was the tool. The final results showed that 70% use teaching strategies for the development of educational process which is satisfactory. Later the interpretation of the results will be compared to the hypothesis. It was concluded that the strategies discussed facilitate learning and help in knowledge acquisition and achieving meaningful learning in students. Teachers were recommended to know and apply the proper teaching strategies; and students to link theory to practice so as to improve their academic performance in the subject of Physics and Chemistry